CONTEMPORARY PRACTICES OF PUBLIC AUTHORITIES’ COOPERATION AT THE CENTRAL AND LOCAL LEVEL - Khashiyeva L.V. (Pressing Problems of Public Administration, 2018)
The article is devoted to the study of features of contemporary models of cooperation between public authorities at the central and local level in the foreign countries. Possible ways of application of the best practices at the context of local government reform in Ukraine are defined.